Analisis Sistem Informasi Manajemen Proyek Menggunakan Metode Waterfall Berbasis Web - Dastin Ramadhani; Muhammad Fakih (Journal of Information Systems and Business Technology, 2025)
The purpose of this study was to see how web-based project management systems, used to manage activities such as project assignments, reporting, and monitoring, function. The study investigated various project management applications used by organizations and highlighted several issues such as inflexible workflows, lack of system integration, and non-user-friendly interfaces. The study went through the stages of requirements analysis, system design, solution simulation, and performance testing using a blackbox approach using the Waterfall methodology. The results of the analysis showed that although the system could perform its basic functions, there were several elements that needed to be improved to increase the efficiency and effectiveness of overall project management.